{Synthesis of methylene-bridged polycyclic aromatic hydrocarbons: an efficient, double Friedel-Crafts cyclization approach to 11H-benz[bc]aceanthrylene} - Gimisis, Thanasis; Kampf, Jeff W.; Koreeda, Masato (J. Org. Chem., 1993)
A five-step synthesis of 3-methylcholanthrene (1) has been achieved starting from 5-methylhomophthalic anhydride and N,N-diethyl-1-naphthamide in 55{%} overall yield. Treatment of a solution of the preformed lithium enolate of 5-methylhomophthalic anhydride (3) with an equimolar solution of 2-lithio-1-naphthamide (4), followed by acid hydrolysis, provides cleanly the spirobislactone 5 in 80{%} overall yield. In addition, the synthesis features a unique, highly selective double Friedel-Crafts cyclization of the aryl diacid 2 with PPA to give rise, after acetylation, to keto acetate 6. © 1993 America Chemical Society.